PENINGKATAN PRODUKSI GAS HIDROGEN (H2 )DAN ETANOL PADA Bacillus pumilus DENGAN MUTASI MENGGUNAKAN Ethyl Methane Sulfonate (EMS) DAN SELEKSI DENGAN METODA PROTON SUICIDE - Trismilah, Trismilah; AR, Mahyudin (BERITA BIOLOGI, 2009)
Mutation by using Ethyl Methane Sulphonate (EMS) was carried out in the study of the enhancement of H2 and ethanol production in Bacillus pumilus.Target mutant was selected by using proton suicide method. Bacterial suspensions was spread into agar minimal U medium containing 13 or, 14, 15 and 16 u.1 of Ethyl Methane Sulphonate (EMS) and incubated at 37 C for 3, or 4 , or 5, or 6 hours.The method of proton suicide was applied by the addition of equimolar of 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 75, 100, 125, 150, 175, 180, 185, 190, 195, 200 mM NaBr and NaBrO3.Triphenyl tetra chloride (TTC) was also added as indicator into agar plate in order to distinguish between wild type and mutants. Fermentation was carried out using glycerol complex medium.Hydrogen gas(H,) contain was determined by the replacement of NaCI solution in cylindrical glass and the ethanol was measured by gas chromatography. After mutation, several mutants were observed. In Mutant ( Asp8) which was obtained by treatment of 195 equimolar of NaBr and NaBrO,, production of ethanol and H2 were higher 10 fold and 1.13 fold, respectively compare to the wild type while acids production decreased. The data indicated that mutation might provoke metabolic alteration especially in acid production.